An Approach Towards Structure Based Antimicrobial Peptide Design for Use in Development of Transgenic Plants: A Strategy for Plant Disease Management - Ilyas, Humaira; Datta, Aritreyee; Bhunia, Anirban (Current Medicinal Chemistry, 2017)
Antimicrobial peptides (AMPs), also known as host defense peptides (HDPs), are ubiquitous and vital components of innate defense response that present themselves as potential candidates for drug design, and aim to control plant and animal diseases. Though their application for plant disease management has long been studied with natural AMPs, cytotoxicity and stability related shortcomings for the development of transgenic plants limit their usage. Newer technologies like molecular modelling, NMR spectroscopy and combinatorial chemistry allow screening for potent candidates and provide new avenues for the generation of rationally designed synthetic AMPs with multiple biological functions. Such AMPs can be used for the control of plant diseases that lead to huge yield losses of agriculturally important crop plants, via generation of transgenic plants. Such approaches have gained significant attention in the past decade as a consequence of increasing antibiotic resistance amongst plant pathogens, and the shortcomings of existing strategies that include environmental contamination and human/animal health hazards amongst others. This review summarizes the recent trends and approaches used for employing AMPs, emphasizing on designed/modified ones, and their applications toward agriculture and food technology.
Keywords: Antimicrobial peptides